Determinan Tingkat Kemiskinan pada Kabupaten Kota di Provinsi Nusa Tenggara Timur Tahun 2011-2018 dalam Perspektif Ekonomi Islam - Rahmiyanti, Desi; Wicaksono, Yanuardi (Al-Buhuts, 2023)
Poverty or the number of people living under the poverty line is a big issue being faced by most of developing countries including Indonesia. Poverty refers to a condition in which someone is not capable of fulfilling the primary needs. The percentage of population in East Nusa Tenggara is in the third highest rank after West Papua and Papua. The aim of this study is to observe the impacts of Gross Regional Domestic Product (GRDP), Human Development Index (HDI), population rate and Open Unemployment Rate on the poverty in regencies/cities in East Nusa Tenggara in 2011-2018 in the Islamic economic perspective. This is a quantitative research in which it used the sample in the form of secondary data related to GRDP per capita, HDI, population rate, and Open Unemployment Rate in 21 regencies/cities in East Nusa Tenggara in the period of 2011-2018. The data analysis method used was PVECM (Panel Vector Error Correction Model) to estimate the long-term and short-term impacts between the independent and dependent variables. The results of this study showed that GRDP in the short-term and long-term had a negative impact on the poverty. Meanwhile, HDI significantly had long-term negative impact and insignificant short-term positive impact and the population rate in both short-term and long term brought a significantly positive impact. Furthermore, Open Unemployment Rate in the long term brought a negative impact and in the short term it brought positive impact on poverty. Then, simultaneously, variables GRDP, HDI, population rate and Open Unemployment Rate both in a long term and in a short term brought a positive impact on the poverty with the long term probability values of statistic F of 0,000000 and the one in the short term of 0,001108.